Protection of The Reproductive Rights of Female Workers - Kamelia Karim Dwi Putri; Marwati Riza; Sakka Pati (Al-'Adl, 2022)
The study aims to analyze the protection of the reproduction rights of female workers through preventive and repressive legal protection facilities. This research uses empirical legal research methods by observing various facts in the field in the form of research that begins with literature studies as an initial data source. The author conducts observations and interviews to obtain data or materials relevant to the object studied. Based on the study results, it can be concluded that the protection of the reproduction rights of female workers is further regulated in employment agreements, collective labor agreements, or company regulations are still many who ignore the rules contained in the Labor Act. Employment Agreement only further regulates what is not regulated in the Employment law. When the Employment Agreement, Collective Labor Agreement, or Company Regulation rules conflict with the Law, the agreement is null and void.